Mediterranean-style diet and risk of ischemic stroke, myocardial infarction, and vascular death: the Northern Manhattan Study. - Gardener, Hannah; Wright, Clinton B; Gu, Yian; Demmer, Ryan T; Boden-Albala, Bernadette; Elkind, Mitchell S V; Sacco, Ralph L; Scarmeas, Nikolaos (Am J Clin Nutr, 2011)
BACKGROUND: A dietary pattern common in regions near the Mediterranean appears to reduce risk of all-cause mortality and ischemic heart disease. Data on blacks and Hispanics in the United States are lacking, and to our knowledge only one study has examined a Mediterranean-style diet (MeDi) in relation to stroke. OBJECTIVE: In this study, we examined an MeDi in relation to vascular events. DESIGN: The Northern Manhattan Study is a population-based cohort to determine stroke incidence and risk factors (mean ± SD age of participants: 69 ± 10 y; 64% women; 55% Hispanic, 21% white, and 24% black). Diet was assessed at baseline by using a food-frequency questionnaire in 2568 participants. A higher score on a 0-9 scale represented increased adherence to an MeDi. The relation between the MeDi score and risk of ischemic stroke, myocardial infarction (MI), and vascular death was assessed with Cox models, with control for sociodemographic and vascular risk factors. RESULTS: The MeDi-score distribution was as follows: 0-2 (14%), 3 (17%), 4 (22%), 5 (22%), and 6-9 (25%). Over a mean follow-up of 9 y, 518 vascular events accrued (171 ischemic strokes, 133 MIs, and 314 vascular deaths). The MeDi score was inversely associated with risk of the composite outcome of ischemic stroke, MI, or vascular death (P-trend = 0.04) and with vascular death specifically (P-trend = 0.02). Moderate and high MeDi scores were marginally associated with decreased risk of MI. There was no association with ischemic stroke. CONCLUSIONS: Higher consumption of an MeDi was associated with decreased risk of vascular events. Results support the role of a diet rich in fruit, vegetables, whole grains, fish, and olive oil in the promotion of ideal cardiovascular health.
Keywords: African Continental Ancestry Group; Aged; Brain Ischemia; Diet Surveys; Diet, Mediterranean; European Continental Ancestry Group; Female; Hispanic Americans; Humans; Incidence; Male; Middle Aged; Myocardial Infarction; New York City; Proportional Hazards Models; Prospective Studies; Questionnaires; Risk Factors; Stroke; Vascular Diseases